MORAL-ETHICAL DILEMMAS AND CULTURAL CONTEXT IN TAHIR MALIK’S NOVEL «SHAYTANAT» (DEVILDOM) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article is devoted to a comprehensive analysis of Tahir Malik’s work “Shaytanat”, focusing on the sociocultural, psychological, and moral-ethical facets that manifest within the context of character interpretation and their interactions. The research is grounded in a deep analytical approach, ensuring a detailed examination of multidimensional interpretations of the work’s content. During the analysis, key characteristics of the characters, as well as their intrinsic motivations, conflicts, and relationships, were identified. Particular attention is paid to the confrontation between moral and amoral principles in the lives of the main characters, as well as the role of patriotism and love for the homeland. The study’s findings allow for a delve into the deeper layers of the text, revealing the unique features of the author's perspective on the sociocultural processes of his era.